Os limites imanentes ao conceito de meio ambiente como bem de uso comum do povo - Melo, Noerci da Silva (My University, 2014)
The human being is the biggest predator of himself and the surrounding environment. The magnitude and the gravity of the problems created by this predatory behavior, as time goes by, made people conscious of the need of a new ecological awareness, with a focus on the environment and its preservation as a way to protect wildlife. The concept of environment is uncertain. In 1988 the Federal Constitution, however, innovating in terms of well-being, defined environment as a public property to be used by the people which is essential for a healthy life , this way creating a new category of public properties, formed by properties which are neither public nor private, but of general interest. As a consequence of this new concept, the Constitution established limits for the use of the environment immanent limits, in the right amount to guarantee a healthy way of life.
O homem é o maior predador da natureza e de si mesmo. A gravidade dos problemas gerados por essa atitude predatória, com o passar do tempo, despertou para a necessidade de uma consciência ecológica, voltada à preservação do meio em que prolifera a vida. O conceito de meio ambiente é incerto. A Constituição Federal de 1988, contudo, inovando em matéria de bem público, definiu meio ambiente como bem de uso comum do povo e essencial à sadia qualidade de vida , criando uma terceira categoria de bens, formada por bens que não são públicos nem particulares, mas de interesse público. Como conseqüência desse novo conceito, a Carta Constitucional estabeleceu limites à utilização do bem ambiental limites imanentes , na medida necessária para garantir uma vida saudável.
Keywords: Direito; Preservação; Meio ambiente; Limites imanentes; Direito ambiental; Preservation; Environment; Immanent limits; Enviromental law